Policy Analysis and Role of Livestock Subsector in the Development at Purworejo Regency, Central Java - Agus Setiawan; Budi Guntoro; F. Trisakti Haryadi (Faculty of Animal Science, Universitas Brawijaya, 2022)
This study aims to analyze the livestock subsector policy in Purworejo Regency in the 2016-2021 period and determine the leading subsector in the agricultural sector that can be developed in Purworejo Regency. This study uses descriptive analysis methods and quantitative analysis to determine the role of the livestock sub-sector by calculating Location Question (LQ), Shift Share (SS), and Klassen Typology. The results of this study indicate that policies in the livestock sub-sector, namely optimizing the livestock sub-sector and limiting large-scale livestock business activities in residential areas, are supported by 2 programs, namely the program to increase livestock production and the application of agricultural technology. The second policy is the application of superior agro-input and Agro Farm commodities supported by the Agricultural and Livestock Commodity Agribusiness program. The results of the Location Quotient (LQ) analysis of the livestock sub-sector are 1.24 including the base sector, meaning that the sector plays a more important role in the economy in an area compared to the area above it and is an important sub-sector in Purworejo district. The results of the shift-share analysis showed a negative result (-0.33) which was further analyzed by the Klassen Typology method, the livestock sub-sector is in quadrant III, which means it is a rapidly growing sub-sector but the sector's competitiveness is low compared to other sectors. This sector is included in the base sector, meaning that the sector plays a more important role in the economy in a region compared to the area above it and is an important sub-sector in the Purworejo district. The results of the shift-share analysis showed a negative result (-0.33) which was further analyzed by the Klassen Typology method, the livestock sub-sector is in quadrant III, which means it is a rapidly growing sub-sector but the sector's competitiveness is low compared to other sectors. This sector is included in the base sector, meaning that the sector plays a more important role in the economy in a region compared to the area above it and is an important sub-sector in the Purworejo district. The results of the shift-share analysis showed a negative result (-0.33) which was further analyzed by the Klassen Typology method, the livestock sub-sector is in quadrant III, which means it is a rapidly growing sub sector but the sector's competitiveness is low compared to other sectors.